Palaeoseismicity in the Siwaliks: occurrence of major seismic events in the Himalayas of west Nepal - Mascle, Georges H.; Chalaron, Edouard; Gajurel, A. P.; Leturmy, Pascale; Mugnier, Jean Louis (Journal of Nepal Geological Society, 1998)
The Siwaliks represent both the Neogene-Quaternary foreland thrust belt of the Himalaya and the sedimentary series of fluvial origin that have been deposited in a flexural foreland basin near the mobile front of the Himalayan range and have been successively incorporated by thrusting to the structural edifice. The still active deformation of the Siwalik prism occurs through both the seismic and aseismic regime. Structures of syn-sedimentary liquefaction are observed in the Upper Siwaliks of the well dated Surai Khola section of western Nepal. Two particularly thick liquefied layers occur near the base of the Dobata Formation of around 4.1 Ma in age and are also observed in the Babai Khola section about 120 km west of the Surai Khola. These data are compared with the extension of liquefaction induced by modem earthquakes in the area (mainly the 1934 Bihar-Nepal earthquake) and plotted on two graphs: 1- maximum epicentre distance from liquefied sites versus magnitude of earthquake; 2- thickness of liquefied layers versus earthquake intensity. All the results agree with the occurrence of major paleoearthquakes in the area.